Radiotherapy Plus Chemotherapy Is Associated With Improved Survival Compared to Radiotherapy Alone in Patients With Primary Vaginal Carcinoma: A Retrospective SEER Study - Zhou, Wei-li; Yue, Yang-yang (Frontiers in Oncology, 2020)
ABSTRACT Background: The efficacy of radiotherapy plus chemotherapy (RTCT) versus radiotherapy alone (RT) in the treatment of primary vaginal carcinoma has been controversial. We aimed to evaluate the up-to-date efficacy of RTCT on primary vaginal carcinoma in a real-world cohort. Methods: We performed a retrospective analysis in patients with primary vaginal carcinoma retrieved from the Surveillance, Epidemiology, and End Results Program database from 2004 to 2016. Kaplan-Meier survival curves were plotted and compared by the log-rank test. Inverse probability weighting (IPW)-adjusted multivariate Cox proportional hazards and Fine-Gray competing-risk model was applied. Results: Of the 1813 qualified patients with primary vaginal carcinoma from 2004 to 2016, 1137 underwent RTCT and 676 underwent RT. The median survival time was 34 months for the RT group and 63 months for the RTCT group. RTCT was significantly associated with improved overall survival (unadjusted HR=0.71, 95% CI 0.62-0.82, p<0.001; adjusted HR=0.73, 95% CI 0.63-0.84, p<0.001) and cancer-specific survival (unadjusted sHR=0.81, 95% CI 0.69-0.95, p=0.012; adjusted sHR=0.81, 95% CI 0.69-0.96, p=0.016). Age, histological type, tumor size, surgery, and FIGO stage were all independent prognostic factors for survival (p <0.05 for all). Subgroup analysis demonstrated that RTCT was significantly associated with better survival in most subgroups, except for those with adenocarcinoma, tumor size <2 cm, or FIGO stage I. Moreover, sensitivity analysis did not alter the beneficial effects of RTCT. Conclusion: RTCT is significantly correlated with prolonged survival in patients with primary vaginal carcinoma. RTCT should be applied to most patients with primary vaginal carcinoma instead of RT alone, except for those with adenocarcinoma, tumor size <2 cm, or FIGO stage I.